Modelling, Design and Construction Of A Multipurpose Anechoic Chamber - Chung, Boon Kuan (2003)
A multipurpose anechoic chamber that operates over a very wide frequency range from 30 MHz through 18 GHz has been designed and constructed at the Faculty of Engineering of Multimedia University. An innovative design technique has been developed, giving rise to the construction of an asymmetrical-shaped anechoic chamber which fulfils the different requirements for various measurement needs using lower cost materials. The facility can be used for EMC tests, antenna measurements, monostatic and bistatic RCS measurements, RF transceiver testing, calibration of scatterometer, and other electromagnetic research experiments. It is suitable for both industrial use and basic research.